Role of interventional pain management in patients with chronic pelvic pain. Issue 3 (2nd July 2020) - Hasoon, Jamal; Urits, Ivan; Orhurhu, Vwaire; Viswanath, Omar; Aner, Musa
Abstract: Patients with chronic pelvic pain are often referred to a variety of specialists in gynecology, urology, and gastroenterology with the hope of finding a diagnosis and treatment. We describe a 51-year-old woman with long-standing chronic pelvic pain secondary to endometriosis who was successfully treated with superior hypogastric plexus blocks. Physicians should consider referring patients to interventional pain specialists for assistance with pain control after thorough diagnostic evaluation.